In vitro susceptibilities of 393 recent clinical isolates to WIN 49375, cefotaxime, tobramycin, and piperacillin. - Pohlod, D J (1984)
The in vitro susceptibilities of 393 recent clinical isolates to WIN 49375, a new quinolone derivative, were determined and concurrently tested with cefotaxime, tobramycin, and piperacillin. In general, members of the family Enterobacteriaceae were not as susceptible to tobramycin and piperacillin as they were to WIN 49375. Methicillin-resistant and -susceptible Staphylococcus aureus were equally susceptible to WIN 49375.